Identification of common indicators of hospital performance evaluation models: A scoping review - Vahid Rasi; Bahram Delgoshaee; Mohammahreza Maleki (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Hospitals in developed countries allocate itself about 40% of health-care costs and in developing countries up to 80%. In this study, researchers reviewed the related article in the field of the hospitals' performance evaluation due to the identification of common indicators used in different models with the aim of providing simple list for evaluating hospitals' performance to the researchers who are interested to these issues. METHODS: The databases for the search included Medline, Google Scholar, and Scopus. A search strategy leads to the extraction of 403 related articles that after the removal of inappropriate and duplicate articles, 42 studies were selected for the scoping review. RESULTS: This scoping review showed that 9 of 42 selected articles use data envelopment analysis model, 6 of them Pabon Lasso model, 3 of them balanced scorecard, 3 of them organizational excellence model, and the remaining articles used key performance indicators to evaluate hospital performance. A process approach was used to categorize the common indicators because the literature review indicated that common indicators mainly evaluate data, process, output, or impact of performance. The findings included 36 input, 39 process, 27 output, and 8 impact common indicators for evaluating performance. DISCUSSION: This scoping review of related literature indicated that despite differentiation in the time and place of past studies in the field of performance evaluation models, there are some indicators that are common in most popular performance evaluation models. These simple lists can apply for evaluation of hospitals' performance instead of complicated models.